The Israel-Palestine conflict : parallel discourses - Matthews, Elizabeth G. (UCLA Center for Middle East Development (CMED) series, 2011)
The Israel-Palestine conflict is frequently characterised by the violence between the two sides, beneath€which lie a whole series of issues and disagreements. This book uniquely brings together Israeli and Palestinian viewpoints on key topics, providing an invaluable guide to the latest thinking on the major topics that the peace process will be based around.